Perancangan Virtual Tour Panorama 360 Berbasis Video Di Museum Sri Baduga Bandung Sebagai Media Pembelajaran Sejarah Dan Kebudayaan Untuk Siswa SMP-SMA Di Kota Bandung - Nichi Hana Karlina; Adjie Bagas Nugraha (Universitas Informatika dan Bisnis Indonesia, 2022)
The development of technology shows that the technology forces human to do everything and anything using any known technology. So many great things and functions that can be used by using technology so that humans can do everything easier. The plan of this design was aimed to make a Virtual Tour of Museum Sri Baduga Kota Bandung based on 360 video that have a function for education purpose for students of JHS-HS, also with the making of some support media. This part of design was made by using quantitative and qualitative approach. The data was combined by using online questionnaires and an interview. The Result shows that a Virtual Tour can be a very effective and interesting tools to learn especially for the audience.